2020
DOI: 10.1002/ange.202004550
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Like Properties in Macrocycles above MW 1000: Backbone Rigidity versus Side‐Chain Lipophilicity

Abstract: Large macrocyclic peptides can achieve surprisingly high membrane permeability,a lthough the properties that govern permeability in this chemical space are only beginning to come into focus.W eg enerated two libraries of cyclic decapeptides with stable cross-b conformations,and found that peptoid substitutions within the b-turns of the macrocycle preserved the rigidity of the parent scaffold, whereas peptoid substitutions in the opposing b-strands led to "chameleonic" species that were rigid in nonpolar media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 47 publications
(27 reference statements)
5
25
1
Order By: Relevance
“…Hence, various molecular scaffolds in this chemical space have been systematically investigated to measure the degree of impact of flexibility and rigidity on membrane permeability. 23,37,39,76 CsA has attracted interest in biological applications for decades and has recently been reinvestigated as a representative chameleonic macrocycle. 35 In general, CsA derivatives show high membrane permeability, but it is reduced when polarity is increased or chameleonic behavior is lost.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, various molecular scaffolds in this chemical space have been systematically investigated to measure the degree of impact of flexibility and rigidity on membrane permeability. 23,37,39,76 CsA has attracted interest in biological applications for decades and has recently been reinvestigated as a representative chameleonic macrocycle. 35 In general, CsA derivatives show high membrane permeability, but it is reduced when polarity is increased or chameleonic behavior is lost.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A recent report by Lokey and co-workers indicated that both rigid and chameleonic macrocyclic peptides (i.e., libraries A and B, respectively) showed high membrane permeability. 23 Other rigid macrocycles, such as rifampicin 76 and cyclic hexapeptides 39 also demonstrated membrane permeability and oral bioavailability. An in vivo PK evaluation of CsO, a macrocycle that is more rigid than CsA, exhibited an approximately 2-or 3-fold decrease in oral bioavailability (F = 12 ± 0.3%), while the PAMPA permeability decrease was 7fold compared to CsA.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, these more flexible analogues had decreased or similar membrane permeabilities compared to CsA. At least for this small sample set of cyclosporins, with the assumption that changing the lipophilicity has no effect on the permeability, 105 this suggests that some degree of structural integrity is necessary for optimal cyclosporin membrane permeability. Models that take into account this structure−permeability relationship are needed.…”
Section: ■ Overview Of Cyclosporin Structure and Permeabilitymentioning
confidence: 82%
“…Many studies have proposed that the conformational flexibility of cyclosporins may be one factor that aids permeability through membranes, 37,66,75 although recent work suggests a more complicated, interdependent relationship among peptide flexibility, lipophilicity, and membrane permeability. 105 May increased the flexibility of CsA by substituting sarcosine (N-methylglycine, MeGly) into residues 4 and 6 of CsA, respectively. 103 Sarcosine is able to sample significantly more regions of ϕ/ψ backbone dihedral space compared with non-Gly amino acids.…”
Section: ■ Overview Of Cyclosporin Structure and Permeabilitymentioning
confidence: 99%